Revisiting the arcs of integration: Cross‐validations and extensions - Schoenherr, Tobias; Swink, Morgan (Journal of Operations Management, 2012)
AbstractThis paper revisits Frohlich and Westbrook's arcs of integration concept [Arcs of integration: an international study of supply chain strategies. Journal of Operations Management 2001, 19 (2) pp. 185–200]. Using survey responses from 403 supply chain professionals, we compare the arcs of integration group memberships generated with our sample to the original study, rationalize the classification scheme, and assess the impact of supply chain integration strategies on quality, delivery, flexibility and cost performance. In doing so we cross‐validate Frohlich and Westbrook's framework with a more recent and broader sample of data utilizing multi‐dimensional performance measures collected from supply chain managers. We ground these relationships in the relational and resource‐based views of the firm. We also extend Frohlich and Westbrook's study by investigating the moderating role of internal integration on the relationships between arcs of integration and performance. In accordance with information processing theory, the results indicate that internal integration strengthens the positive impacts of external integration on both delivery and flexibility performance. However, the theory is not supported for either quality or cost performance. Overall, our study confirms and extends the work of Frohlich and Westbrook, augments theories used to describe supply chain integration efforts, and provides practical implications for managers.